Multidrug resistance of tumor cells: some new trends in research - A. A. Stavrovskaya; G. P. Guens (Успехи молекулярной онкологии)
Multidrug resistance (MDR) of tumor cells is the resistance to a broad spectrum of structurally unrelated cytotoxic drugs with different mechanisms of action. One of the main causes of MDR phenotype is the activity of ATP-binding cassette transporters (ABC transporters). ABC transporters efflux toxic compounds from the cells. All living cells contain ABC transporters. This review is dedicated to the studies of three-dimensional structure of ABC transporters, to the data concerning MDR evolution in tumor cell populations. Some information about molecular mechanisms of MDR evolution is also presented.